APPLICATION OFVISUALTEST METHODS LOADED ELEMENTS OF ROTATING MACHINERY FLOWTOASSESS THEIR CONDITION - Jan WARCZEK; Mateusz JUZUŃ (Scientific Journal of Silesian University of Technology. Series Transport)
The article presents the aims and objectives of the process of non-destructive testing of turbine aircraft engines using visual methods indirect use of endoscopy. Presents brief characteristics of the construction of engines tested, analyzed the diagnostic procedures used in non-destructive testing methods are shown diagnostic equipment used in research. The paper presents examples of the results of diagnostic checks obtained for the test aircraft engine.